Synthesis, Characterizationand Spectroscopic Studies of 2-{(E)-Hydroxyphenyl)imino]methyl}Phenol Schiff Base with Some Metal Complexes. - Shamkhy, Eman Turky (Al-Nahrain Journal of Science, 2018)
A Schiff base ligand 2-{(E)-[2-hydroxyphenyl)imino]methyl}phenol [LF] was prepared by condensation of salicylaldehyde with 2-aminophenol. The [LF] ligand was characterized by using melting point measurement, F.T.IR and UV-Vis spectroscopy. New series of transition metal complexes of Cu (II), Co (II) and Rh (III) ions were synthesized with this Schiff base. The complexes were characterized by using FTIR, UV-Vis spectroscopy, metal analysis spectrophotometer, conductivity and magnetic susceptibility measurements. The metal coordinated with Schiff base through nitrogen azomethine and phenolic hydroxyl oxygen atoms of the ligand. Magnetic susceptibility data coupled with electronic spectra and suggest a square planar geometry for the Cu(II) complex and octahedral structure for the Co(II) and Rh(III) complexes.